2020
DOI: 10.1177/0950422220909795
|View full text |Cite
|
Sign up to set email alerts
|

The distinct value of humanities students to employers in student consultancy projects

Abstract: This case study analyzes the use by high-profile employers of the brainpower of nearly 1400 humanities undergraduates through “live” projects. At the Faculty of Humanities of Leiden University, a cohort of hundreds advises a set of public, private, and third sector organizations each year in a capstone course within the multidisciplinary Bachelor of Arts in International Studies program. In this course, aptly named PRactising International Studies (PRINS), students have, in teams, successfully consult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…They can be implemented as part of a course (Bak, 2011) or as an alternative to the more established dissertation (Ardley & Taylor, 2010), either with for-profit or non-profit clients (Desai & DeArmond, 2021). Research on consultancy projects has been shown to build bridges between higher education and industry, as well as enhancing employability (Koendjbiharie, 2020). Even though student challenges share similarities with consultancy projects, the student challenge is shorter term and is more evolved around the early stages of an innovation process.…”
Section: Student Challenges and Their Pedagogical Underpinningsmentioning
confidence: 99%
“…They can be implemented as part of a course (Bak, 2011) or as an alternative to the more established dissertation (Ardley & Taylor, 2010), either with for-profit or non-profit clients (Desai & DeArmond, 2021). Research on consultancy projects has been shown to build bridges between higher education and industry, as well as enhancing employability (Koendjbiharie, 2020). Even though student challenges share similarities with consultancy projects, the student challenge is shorter term and is more evolved around the early stages of an innovation process.…”
Section: Student Challenges and Their Pedagogical Underpinningsmentioning
confidence: 99%
“…They can be implemented as part of a course (Bak, 2011) or as an alternative to the more established dissertation (Ardley & Taylor, 2010), either with for-profit or non-profit clients (Desai & DeArmond, 2021). Research on consultancy projects has been shown to build bridges between higher education and industry, as well as enhancing employability (Koendjbiharie, 2020). Even though student challenges share similarities with consultancy projects, the student challenge is shorter term and is more evolved around the early stages of an innovation process.…”
Section: Student Challenges and Their Pedagogical Underpinningsmentioning
confidence: 99%